1990
DOI: 10.3168/jds.s0022-0302(90)78972-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fat Supplementation and Immature Alfalfa to Concentrate Ratio on Lactation Performance of Dairy Cattle

Abstract: Forty-six multiparous Holstein cows were assigned 5 d postpartum to a completely randomized design employing a 2 x 3 factorial treatment arrangement. Factors were 0 or 5% added prilled fat (DM basis) substituted for shelled corn and alfalfa silage fed in forage-to-concentrate ratios of 45:55, 64:36, and 84:16 (DM basis). Interactions between fat and forage level were not observed for any of the parameters measured. Energy density, calculated using data from a digestibility trial, was similar between 45:55 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
3
21

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 29 publications
2
32
3
21
Order By: Relevance
“…In contrast to studies where extra glycogenic nutrients were fed, 13 [60,61,66,[68][69][70][71][72][73] out of 14 reported studies found a decrease in plasma NEFA levels. Plasma BHBA levels increased after feeding extra lipogenic nutrients in five out of eight studies [68,69,74,75]. Extra glycogenic nutrients were related to a decrease in plasma BHBA levels in eight out of nine reported studies [61,69,70,72,74,76].…”
Section: Effect Of Lipogenic and Glycogenic Nutrients On Blood Metabomentioning
confidence: 89%
See 2 more Smart Citations
“…In contrast to studies where extra glycogenic nutrients were fed, 13 [60,61,66,[68][69][70][71][72][73] out of 14 reported studies found a decrease in plasma NEFA levels. Plasma BHBA levels increased after feeding extra lipogenic nutrients in five out of eight studies [68,69,74,75]. Extra glycogenic nutrients were related to a decrease in plasma BHBA levels in eight out of nine reported studies [61,69,70,72,74,76].…”
Section: Effect Of Lipogenic and Glycogenic Nutrients On Blood Metabomentioning
confidence: 89%
“…Apart from an increase due to higher dietary fat content [69,74,75], plasma BHBA were also elevated with increasing dietary forage level [75]. Ruppert et al [68] found no increase in BHBA, as an indicator of NEB, when fat was added to a corn silage diet, in contrast to an alfalfa silage diet.…”
Section: Effect Of Lipogenic and Glycogenic Nutrients On Blood Metabomentioning
confidence: 99%
See 1 more Smart Citation
“…Aumentar a densidade de energia das dietas pode auxiliar na redução do balanço energético negativo, pois as dietas passam a atender à demanda de energia para produção de leite (Jerred et al, 1990). Palmquist (1988) observou que, em dietas com 8% de EE na MS, parte da EM (15 a 20%) foi oriunda de ácidos graxos de cadeia longa (AGCL).…”
unclassified
“…Como exemplo, pode-se citar o estudo de Wu et al (1993) utilizando gordura protegida (sais cálcicos de óleo de palma), sebo ou ácidos graxos cristalizados (prilled fat) em nível de 2,5% sobre uma dieta com 3,7% de ácidos graxos, contendo 7,2% de Tabela 4 -Composição em ácidos graxos (g/100 g de gordura) das fontes de gordura Wu et al (1993), Grummer (1988), Shauff & Clark (1989), Jerred et al (1990) e Palmquist (1991 não encontraram efeito da suplementação na digestibilidade da fibra. Também não verificaram alterações na fermentação ruminal e na digestibilidade dos nutrientes com a adição de 2,2% de sebo em dietas contendo 10% de grãos de soja.…”
Section: Table 3 -Apparent Digestibility Coefficients (%) Of Dry Mattunclassified